Retrospective analysis of Quality of Life for patients received Prosthetic limbs to overcome their Physical Disability - Moula Bakhsh, Maryam; Farukh, Mehwish; Shareef, Akram; Somroo, Nabila; Jabeen, Naila; Muhammad Imran (International Journal of Endorsing Health Science Research, 2020)
Background: Quality of life (QoL) is affected by physical and psychosocial parameters after amputation. Aims of Person with amputations are to reintegrate in community and improved mobility, optimum quality of life should be among the top priorities of prosthetic and rehabilitation center. The purpose of the study was to retrospectively assess the QoL of the patient receiving artificial limbs to overcome their physical disability. Methodology: A retrospective cross-sectional study was conducted among 120 lower limb prosthetic users; the study duration was four months. Data were collected using the World Health Organization Quality of Life Instruments (WHOQoL-BREF) questionnaire. SPSS Version 16.0 was used for statistical analysis, Mann-Whitney U test and Kruskal-Wallis test were used to compare domain QoL score. Results: Out of 120 respondents, 66(55%) were early prosthetic users and 54(45%) were late prosthetic users. 61(50.8%) lower limb amputees were availing rehabilitative services and 44(36.7%) were employed. Male participant's mean scores were significantly higher in all domains of QoL as compared to females. There was a significant mean difference among male and female patients concerning physical health (p=0.003), psychological health (p=0.027), social relationship (p=0.005) and environment (p=0.000). There were significant differences in the overall QoL domain and the above-mentioned aspects (p<0.05) among the enrolled patients with different working statuses. There was a significant difference in the environment and overall QoL scored in different age group participants. Conclusion: The findings of the study showed that gender, working status and age have significant influences on the QoL of the patients who received Prosthetic limbs to overcome their Physical Disability.